CONSISE SYNTHESIS AND POTENTIAL ANTI-ANGIOGENIC ACTIVITY OF N-1 SUBSTITUTED INDOLYLCHALCONE HYBRIDS ON CHORIOALLANTOIC MEMBRANE (CAM) ASSAY - WANEGAONKAR, ANJALI M.; BHITRE, MILIND J.; ZAVERI, DILLIP; BAIRAGI, SHRIRAM H. (International Journal of Current Pharmaceutical Research, 2021)
Objective: Synthesis of N-1 Substituted Indolylchalcone Hybrids and evaluation of anti-angiogenic activity using Chorioallantoic Membrane (CAM) Assay. Methods: Claisen-schmidt reaction is used for the synthesis of 30 Indolylchalcone hybrids, it involves condensation of N-1 substituted indole-3-carboxaldehyde and N1 substituted 2-acetyl-benzimidazole. The phase transfer catalyst, a green catalyst such as anhydrous potassium carbonate (K2CO3) and PEG-400 are used in the alkylation and arylation. All synthesized indolylchalcone hybrids were evaluated for their antiangiogenic activity by in vivo-chorioallantoic membrane (CAM) assay method. Results: The synthesized indolylchalcone compounds are evaluated. The morphometric study was carried out as described by Melkonian et al. (2002). The Compounds with code C-2, I-1, I-2 are showing the more potent effect on the dose-dependent assay of CAM. The compounds with code C-1, C-3, E-1 to E-3, M-1 and M-5 shows the significant activity, however, though the compounds with code B-1, B-2, CL-1 and A-5 were showing antiangiogenic effect at 0.1 µM, but does not show any significant activity on dose-dependent assay of CAM. Conclusion: The synthesized Indolylchalcones as shown in the graph possess very good dose-dependent anti-angiogenic activities. The potency of anti-angiogenetic activity shows that methyl>Ethyl>Cl-benzyl>Benzyl>Isobutyl. 2-acetyl benzimidazole analogs have possible future scope to develop as potent angiogenesis inhibitors.